ANTISIPASI DIDAKTIS BERSTRUKTUR KONFLIK KOGNITIF UNTUK MENGATASI HAMBATAN BELAJAR SISWA DALAM MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Yanti Ngudi Lestari; Sugiatno Sugiatno; Agung Hartoyo (UNIVERSITAS TANJUNGPURA, 2020)
This research was backgrounded by the difficulties experienced by junior high school students in understanding the addition and subtraction of integers material. One action chosen to overcome this problem was by designing a didactic anticipation with the cognitive conflict structure. The subjects of this research were the class VII students of SMPN 4 Sungai Pinyuh, of which 5 students were randomly taken as the sample. This research was conducted in two phases, preceded by the pretest to find out the initial difficulties faced by students, followed by intervention in the form of cognitive conflict anticipation, and the posttest to determine whether the designed strategy can reduce the difficulties faced by the students. The results showed that the didactic anticipation with the cognitive conflict structure could facilitate students in understanding the addition and subtraction of integers material.Keywors: Didactic anticipation, Learning obstacles